A Jesuit safari essays and interviews on Fr. James O'Brien, SJ - Velasco, Emmanuel Quintos; Espinosa, Aries Belza; Del Prado, Noel Romero (The Editors, 2014)
It is a collection of anecdotes and reflections shared by individuals who fondly remembers the good Jesuit. The book includes personal stories and moving insights from his former students, fellow Jesuits, and co-workers at the Ateneo de Naga and Ateneo de Manila.